From Land-Use Planning to Mixed-Use Configuration. Similarities and Differences in two Urban Fragments of Barcelona Metropolis - Crosas Armengol Carles; Gómez-Escoda Eulàlia; Villavieja Martinez Enric (Lodz University of Technology Press, 2023)
The city of zoning, inspired by the principles of the Charter of Athens, soon generated some rejection in the urban debate of the second half of the twentieth century. Since then, it has been an increasing awareness of the need for the mixed-use urban composition to remediate the inherited monofunctional areas, looking for more sustainable and more efficient metropolises. Thus, contemporary urban planning and design must provide empirical and objective approaches to the different variables that characterize the city and its fragments. This paper presents a 3-year funded research project linking mixticity and proximity with the aim to understand some of the clues on the mixed-use configuration in compact urban areas. Taking Barcelona as case study, the complex relationship between density, topology and accessibility is explored through an analysis that mixes GIS mapping and morphological drawings of small fragments of the city and its metropolitan area. A series of graphics on selected samples (around 25 hectares extension) depict novel views of the districts and emphasizes differences and similarities among the urban fabrics of the compact city, evaluating the concentration and intensity of different services and programs, looking for new tools for the assessment and promotion of the mixticity in cities.
Keywords: Barcelona; activity; mixed-use; functional mix; diversity; aktywność; wielofunkcyjność; mieszanka funkcjonalna; różnorodność